Social urban:entrepreneurial orientationanddiffusion of innovation - et. al., Nanik Qosidah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to examine the influenced social urban by entrepreneurial orientation and diffusion of innovation. This research applies an exploratory-descriptive design. The research data source was primary data collected by questionnaire. The population and sample consisted of the SMME doers in Indonesia, located in tourism objects, 330 respondents. The findings explained that entrepreneurial orientation improved social urban.Diffusion of innovation significantly contributed the social urban improvement. It was proven with the powers of the SMME doers and the increased diffusion of innovation on tourism objects of Indonesia.